2019
DOI: 10.3389/fncel.2019.00223
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-210-3p Targets RGMA to Enhance the Angiogenic Functions of Endothelial Progenitor Cells Under Hypoxic Conditions

Abstract: Endothelial progenitor cells (EPCs) are multipotential stem cells considered to have immense clinical value for revascularization. However, the clinical application of EPCs has been hampered by their clinical potency in ischemic anoxic environments. This study aimed to explore the effect of microRNA-210 (miR-210) on EPCs under oxygen-glucose deprivation (OGD) conditions. We generated a model of EPCs cultured under OGD conditions to simulate ischemia and explore the expression of miR-210 in vitro … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…Moreover, the impact of miR‐210‐3p expression may function contextually as a regulator of particular targets in response to environmental conditions such as energetic stress and ischaemia (van Rooij et al., 2007; Wilczynska & Bushell, 2015). Others studies have shown that miR‐210‐3p has regulatory roles in cell cycle, angiogenesis, DNA damage repair and immune response (Lu et al., 2019; Pasculli et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the impact of miR‐210‐3p expression may function contextually as a regulator of particular targets in response to environmental conditions such as energetic stress and ischaemia (van Rooij et al., 2007; Wilczynska & Bushell, 2015). Others studies have shown that miR‐210‐3p has regulatory roles in cell cycle, angiogenesis, DNA damage repair and immune response (Lu et al., 2019; Pasculli et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…mir-210-3p regulates non-small cell lung cancer cell proliferation and apoptosis by targeting paired amphipathic helix protein Sin3 transcription regulator family member a (44). mir-210-3p also targets repulsive guidance molecule a to enhance the angiogenic functions of endothelial progenitor cells under hypoxic conditions (45). However, whether mir-210-3p directly regulates BniP3 and aiF is not completely understood.…”
Section: Discussionmentioning
confidence: 99%
“…RGMa is a negative regulator of angiogenesis [ 33 ]. The binding of recombinant RGMa with Neogenin on endothelial cells can significantly reduce endothelial cell proliferation, migration, and formation of vascular endothelium, as well as the level of phosphorylated focal adhesion kinase (p-FAK Tyr397) [ 5 , 33 , 34 ]. In addition, F-actin assembled in the cytoskeleton was also significantly inhibited, thereby inhibiting cytoskeleton reorganization [ 5 ].…”
Section: Role Of Rgma In Cns Pathologymentioning
confidence: 99%